Synthesis of bis-furyl-pyrrolo[3, 4-b]pyridin-5-ones via Ugi–Zhu reaction and in vitro activity assays against human SARS-CoV-2 and in silico studies on its main proteins. Issue 1 (30th November 2022) - Morales-Salazar, Ivette; Montes-Enríquez, Flora P.; Garduño-Albino, Carlos E.; García-Sánchez, M. A.; Ibarra, Ilich A.; Rojas-Aguirre, Yareli; García-Hernández, Montserrat Elemi; Sarmiento-Silva, Rosa Elena; Alcaraz-Estrada, Sofía Lizeth; Díaz-Cervantes, Erik; González-Zamora, Eduardo; Islas-Jácome, Alejandro
Abstract : Six polyheterocycles were studied in vitro against human SARS-CoV-2 finding that one of them exhibited significant activity at initial infection stages, showing prophylactic potential. A second one showed both, prophylactic and therapeutic activity. Abstract : An Ugi–Zhu three-component reaction (UZ-3CR) coupled in one pot manner to a cascade process ( N -acylation/aza Diels–Alder cycloaddition/decarboxylation/dehydration) was performed to synthesize a series of bis-furyl-pyrrolo[3, 4- b ]pyridin-5-ones in 45 to 82% overall yields using ytterbium triflate as a catalyst, toluene as a solvent, and microwaves as a heat source. The synthesized molecules were evaluated in vitro against human SARS-CoV-2 through a time-of-addition approach, finding that compound 1e, at a concentration of 10.0 μM, exhibited a significant reduction at the initial infection stages, thus showing prophylactic potential. On the other hand, it was found that compound 1d, at the same concentration, was significantly active when applied post-infection, thus exhibiting a therapeutic profile. Moreover, compound 1f showed both, prophylactic and therapeutic activity. Then, to understand interactions between synthesized compounds and the main proteins related to the virus, docking studies were performed on spike-glycoprotein, main-protease, and Nsp3 protein, finding moderate to strong binding energies, matching accurately with the in vitro results. Additionally, a pharmacophore model was computed behind further rational drug design.